Stability and electrorheology of ZnO nanofluids in the presence of anionic surfactants - Zaid, H.M. (American Institute of Physics Inc., 2016)
In this research, the preparation of stable ZnO nanofluids has been studied by the interaction of unmodified ZnO nanoparticles with anionic surfactant, and the impact of this on the electrorheological properties of nanofluid. Using laboratory experiments including measurement of sedimentation and adsorption of surfactant, the sedimentation behavior of ZnO nanoparticles was evaluated. The results show that the most stable aqueous dispersions of ZnO nanoparticles (calcined at 500 and 800°C) is obtained with the aid of 0.025 wt sodium dodecylbenzenesulfonate (SDBS), at a fixed concentration of 0.1 wt ZnO. The ZnO@500/SDBS dispersion exhibits better stability at high temperature of 95°C, with the percentage stability of 56.6 compare to 44.2 of ZnO@800/SDBS dispersion. The stabilized nanofluids were then subjected for measuring of electrorehological behaviour using a rotating viscometer attached to a custom-built solenoid coil. The rheological measurements indicated that all the nanofluids exhibit pseudoplastic (shear thinning) behavior. At a low shear rate, the viscosity of 0.1 wt ZnO@500/SDBS dispersion provide an enhancement in the viscosity of nanofluid up to 133 compare to brine as a base fluid. Whereas, ZnO@800/SDBS dispersion shows an increment of 183 in its viscosity under electromagnetic waves. This depicts the role of stability in order to achieve an electrorheological effect by activating dielectric ZnO nanoparticles. Further these investigations explained how the polarization of induced dipoles affects the electrorheology of ZnO nanofluids, by creating chains that align with the applied electric field. Hence the mobility of a stabilized nanofluid can be efficiently controlled by regulating the applied field for EOR purposes. © 2016 Author(s).